A theorem on the structure of a complete set of conformal-like series of conserved quantities for massless fields - Simulik, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We formulate a convenient general method for construating a complets set of comformal-like series of conservation laws of the n th order. As examples, we give all conformal-like series which are generated by symmetric tensors of the third and fourth ranks.